2020
DOI: 10.4236/jwarp.2020.124019
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Irrigation Water Allocation Framework Based on Genetic Algorithm Approach

Abstract: In a world where excessive use and degradation of water resources are threatening the sustainability of livelihoods dependent on water and agriculture, increased food production will have to be done in the face of a changing climate and climate variability. There is a need to make optimal use of the available water resource to maximize productivity. Climate-smart irrigation is aimed at increasing per unit production and income from irrigated cropping systems without having negative impacts on the environment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…e first item represents the cost of the logistics company to distribute a logistics task, the second item represents the cost of the logistics company to transport the logistics task to the cooperative distribution company, and the third item represents the distribution cost required by the cooperative distribution company. e objective function indicates that the points with F > 0 are selected, and the distribution points requiring transshipment are calculated; equation (2) indicates that the transfer point cannot transfer within the company; equation (3) indicates that only one company can be responsible for a demand task; equation (4) indicates that the distribution weight of the distribution company is not greater than the bearing weight of the company; equation ( 5) is an integer constraint.…”
Section: 􏼨 (5)mentioning
confidence: 99%
See 1 more Smart Citation
“…e first item represents the cost of the logistics company to distribute a logistics task, the second item represents the cost of the logistics company to transport the logistics task to the cooperative distribution company, and the third item represents the distribution cost required by the cooperative distribution company. e objective function indicates that the points with F > 0 are selected, and the distribution points requiring transshipment are calculated; equation (2) indicates that the transfer point cannot transfer within the company; equation (3) indicates that only one company can be responsible for a demand task; equation (4) indicates that the distribution weight of the distribution company is not greater than the bearing weight of the company; equation ( 5) is an integer constraint.…”
Section: 􏼨 (5)mentioning
confidence: 99%
“…e continuous production of relevant automation software and website platform has effectively alleviated the conflict between supply and demand of contemporary logistics information, but there are still many defects: first, the sharing rate of logistics resources is very low, and many logistics resources have not been effectively used, resulting in the low utilization rate of logistics resources; the second is the lack of basic flexibility of logistics services (such as failure of service links and lack of replacement efficiency); third, users have relatively little access to logistics information, which makes it difficult for them to explore the most ideal logistics services; fourth, the current logistics information lacks basic transparency and fails to solve the personalized needs of users. If these problems continue to exist, they will directly or indirectly lead to the rise of logistics costs and the significant reduction of service quality [4]. erefore, it is necessary to optimize the logistics allocation, as shown in Figure 1, the transportation management system of multitask scheduling.…”
Section: Introductionmentioning
confidence: 99%
“…The dry season (irrigation) farmers get more profit than rainfed farmers counterparts. This is not unconnected with the high demand for fresh irrigated crops during the dry season [27]. Moreover, a study on the Socio-economic impact of an irrigation project in Taraba State reported similar findings among the farmers in respect of economic gain.…”
Section: Economic Aspect Of Sustainable Irrigation Schemesmentioning
confidence: 60%
“…The dry season (irrigation) farmers get more profit than rain-fed farmers counterparts. This is not unconnected with the high demand for fresh irrigated crops during the dry season [27]. Moreover, a study on the Socio-economic impact of an irrigation project in Taraba State reported similar findings among the farmers Sustainability-Based Review of Irrigation Schemes Performance for Sustainable Crop… DOI: http://dx.doi.org/10.5772/intechopen.103980 in respect of economic gain.…”
Section: Economic Aspect Of Irrigation Schemes Sustainabilitymentioning
confidence: 64%